Spontaneous Germ Cell Apoptosis in Humans: Evidence for Ethnic Differences in the Susceptibility of Germ Cells to Programmed Cell Death - Amiya P. Sinha Hikim; Christina Wang; Yanhe Lue; Larry A. Johnson; X.-H Wang; R. S. Swerdloff (1998)
Spontaneous death of certain classes of germ cells has been shown to be a constant feature of normal spermatogenesis in a variety of mammalian species, including the human. Recent studies on various animal models have demonstrated that apoptosis is the underlying mechanism of germ cell death during normal spermatogenesis. Withdrawal of gonadotropins and/or testosterone further accelerates the germ cell apoptosis. We examined the involvement of apoptosis in the spontaneous loss of germ cells in men. Testicular samples obtained at autopsy from 5 Chinese and 9 non-Hispanic Caucasian men were analyzed. To identify individual germ cells undergoing apoptosis, we used a modified terminal deoxynucleotidyl transferase-mediated deoxy-UTP nick end labeling technique that detects germ cell apoptosis with high sensitivity and specificity. Testicular sections from all 14 subjects exhibited spontaneous occurrence of germ cell apoptosis involving spermatogonia, spermatocytes, and spermatids (apoptotic indexes, 1.6 +/- 0.4 2.5 +/- 0.6, and 5.5 +/- 1.2, respectively). The incidence of spermatogonial (2.8 +/- 0.8 vs. 1.0 +/- 0.2) as well as spermatid (9.3 +/- 2.1 vs. 8.4 +/- 0.9) apoptosis was higher in Chinese than in Caucasian men. A higher incidence of spermatocyte apoptosis was also noted for Chinese (4.4 +/- 1.4) compared to Caucasian (1.9 +/- 0.4) men, but the difference was not statistically significant. These results suggest that germ cell death during normal spermatogenesis in men occurs via apoptosis and provide evidence for ethnic differences in the inherent susceptibility of germ cells to programmed cell death. Our data may also help to explain the greater efficacy of testosterone-induced spermatogenic suppression to azoospermia observed in Asian compared to non-Asian men.